(untitled) (Materiali di Estetica. Terza serie, 2018)
In 1984, the Italian philosopher and psychologist Alfredo Civita (1952-2017) published an essay dedicated to the main interpretations of the comic and the comicalness in the philosophical, psychological, linguistic and literary fields. On the basis of the idea of an substantial irreducibility of the comic to a unitary essence, this paper aims to examine Civita’s interpretations of the thought of Bergson and Freud with regard to the laughter, the wit and the uncanny. What emerges, beyond some specific differences, is the leading role assigned to imagination by both authors.